O corpo como posicionamento de marca na comunicação empresarial - Bambini, Simone Ribeiro de Oliveira (2015)
The corporate culture tends to ignore that the human body exchanges information with the environment where it is inserted and, consequently, it becomes a bodymedia (KATZ & GREINER) between the communication process and its surroundings. At the same time, the conduct regarding to the employees has been reconfigured due to the fact that the body was discovered as a powerful advertising agent. The body has gained a major representation within the business speech, and the companies have held the employees body beyond the geographic limits. As a result, the delimitations between leisure and labor have become a blur. The target project focus on the body role in the organizational communication, and as part of this understanding the body is considered as a container in which the information is supposed to be deposited and retransmitted. According to this point of view, the organizational culture deals with the employees body as a transmission mechanism of the public image which is desired to be disseminated. The aim of the project is to investigate how the internal communication becomes part of the biopolitics that heads us nowadays. As a result, the internal communication gains external visibility when the employees bodies are used as a relevant agent that maintains a close relation with the values that guide the consumer world (LIPOVETSKY & SERROY, 2011). The methodology includes a bibliography review and an exploratory research by means of interviews with doctors directly linked to the companies Unilever, Johnson & Johnson and Editora Abril and also with doctors who are not linked to those companies. It also has some theoretical reference based on the works by Giorgio Agamben (2002, 2004, 2007, 2009); Esposito (2007, 2009, 2010), the Bodymedia Theory (KATZ & GREINER, 2001, 2003, 2005, 2007, 2009, 2010, 2011, 2013), Damásio (1998, 2000, 2004); Pinker (2004) the understanding of happiness according to Freire Filho (2011) and Richard Sennett (2006, 2011)